2015
DOI: 10.1155/2015/239623
|View full text |Cite
|
Sign up to set email alerts
|

CD4+RORγt++ and Tregs in a Mouse Model of Diet‐Induced Nonalcoholic Steatohepatitis

Abstract: Background and Aims. Inflammatory mediators that cross-talk in different metabolically active organs are thought to play a crucial role in the pathogenesis of Nonalcoholic Steatohepatitis (NASH). This study was aimed at investigating the CD4+RORγt+ T-helper cells and their counterpart, the CD4+CD25+FOXP3+ regulatory T cells in the liver, subcutaneous adipose tissue (SAT), and abdominal adipose tissue (AAT) in a high fat diet (HFD) mouse model. Methods. C57BL6 mice were fed a HFD or a normal diet (ND). Liver en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
1
28
1
Order By: Relevance
“…ALT and AST levels are significantly increased after 34–36 weeks. However, this diet induces only minimal fibrosis after extended exposure (36–50 weeks) [ 46 , 47 ]. As was mentioned above, it should be noted that the time of onset and degree of both the metabolic features and NAFLD is dependent of species, strain, sex and composition of gut microbiota, as well as dietary fat content.…”
Section: Dietary Modelsmentioning
confidence: 99%
“…ALT and AST levels are significantly increased after 34–36 weeks. However, this diet induces only minimal fibrosis after extended exposure (36–50 weeks) [ 46 , 47 ]. As was mentioned above, it should be noted that the time of onset and degree of both the metabolic features and NAFLD is dependent of species, strain, sex and composition of gut microbiota, as well as dietary fat content.…”
Section: Dietary Modelsmentioning
confidence: 99%
“…In another study using mice fed with high-fat diet (HFD), there was a significant increase of Th17 cells in the liver ( P  < 0.02) and the abdominal adipose tissue (AAT) ( P  < 0.01), without a concurrent increase of Treg (60). NASH and metabolic alterations occurred in mice-fed HFD, and Th17 cells (either AAT or liver-derived) positively correlated with NASH (60).…”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 99%
“…In another study using mice fed with high-fat diet (HFD), there was a significant increase of Th17 cells in the liver ( P  < 0.02) and the abdominal adipose tissue (AAT) ( P  < 0.01), without a concurrent increase of Treg (60). NASH and metabolic alterations occurred in mice-fed HFD, and Th17 cells (either AAT or liver-derived) positively correlated with NASH (60). Other studies have shown in parallel that the reduction, dysfunction, or disproportionate number of Treg cells contributes to the progression to NASH because Treg cells play a critical role in regulating the inflammatory processes in the liver (24, 29, 30).…”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 99%
“…Despite hepatic steatosis, inflammatory cell infiltration was not present until 19 weeks of HFD intake [19]. While after long-term (34-36 weeks) HFD feeding, significant increases in circulating liver enzyme levels, i.e., alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were observed [19], these mice showed only minor signs of inflammation and fibrosis [21], even after prolonged administration up to 50 weeks [19]. Yet, after chronic feeding (80 weeks) of HFD, which mimics lifetime HFD consumption and enables proper design of treatment options, Velázquez et al [17] demonstrated that mice displayed obesity and insulin resistance.…”
Section: Dietary Murine Modelsmentioning
confidence: 99%